Handbook of the economics of education - Hanushek, Eric A. (Eric Alan), 1943-; Welch, Finis, 1938- (Amsterdam ; London : North-Holland, 2006)
The economics of education reaches back in the direction of understanding what goes on in schools. What factors influence the quality and outcomes of schools? How does institutional structure influence outcomes? How does finance interact with the level and distribution of outcomes?
-- Income and peer quality sorting in public and private schools / Thomas J. Nechyba -- Public intervention in post-secondary education / Thomas J. Kane -- US higher education finance / Michael S. McPherson and Morton Owen Schapiro -- Income contingent loans for higher education : international reforms / Bruce Chapman.
Includes bibliographical references and index.
rua 23/02/15
Loans
Keywords: Education -- Economic aspects -- United States; Education -- United States -- Finance; Wages -- Effect of education on -- United States